Nanocompósitos de nanowhiskers de fibra de mandioca e álcool polivinílico empregando eletrofiação - Souza, Bruno Venson de (2021)
Cassava production is associated with large amounts of solid and liquid wastes that have scarce options to reuse in the industry life cycle. In developing countries, the recycling of cassava waste is a good opportunity for reducing impacts from the limited options linked to environmental issues and associated with the disposal and reutilization of this residue. Cassava starch waste include cellulose, lignin, hemicellulose and proteins in a humid pasta by-product of the industrial processing. As cellulose is an interesting polymer for its crystalline structure, the cassava starch treatment from chemical process like mercerization, bleaching, acid hydrolysis and dialysis foster the extraction of the non-crystalline elements resulting in nanostructures known as nanowhiskers for its two-dimensional nanoscale. The opportunity of reinforcing polymers to form nanocomposites with matrixes such as polyvinyl alcohol (PVA) that are very used in the food and pharmaceutical industry also may promote benefits due to the challenge of artificial polymers chain molecules breaking. This work applied electrospinning processing technique to reinforce PVA matrix with cassava nanowhiskers chemically treated in mass/mass percentages of 0, 1, 2.5 and 5. Electrospinning process applied a tension between 15 to 18kV to the solution of PVA and cassava nanowhiskers using rotative collector. According to FTIR and X-ray diffraction test it was possible to have crystallinity increase of the cassava starch sample with mercerization, bleaching, acid hydrolysis and dialyze on chemical treatment. There were achieved improvements in thermal stability of the solution using 5% nanowhiskers reinforcement compared to the other samples electrospun. Polymer process generated fibers ranging 150 to 600 nanometers diameter from calibrated technical and environmental conditions to have electrospun nanofibers. Chemical treatment of the cassava waste is associated with the use of considerable amount of resource that generate low productivity of final material after electrospinning process. Cassava starch treatment acquired mass/mass productivity of 13,5% and at the conclusion of the electrospinning process percentages of 0,91% and 4,55% mass/mass productivity using rotative collector in PVA matrix reinforced with nanowhiskers.